Impact of social policy on the self-sustainable development of grassroots social organizations in the Tacna region - Loza Ticona, Renzi Marilu (2013)
Objetive: The objective is to determine the impact of the Social Policy to Combat Poverty in self-sustaining development of Basic Social Organizations in the Tacna Region, and considers the hypothesis: If, Social Policy to Combat Poverty guidelines is action welfarism and paternalism. Then in the Tacna Region Social Policy poverty has a negative impact on self-sustaining development of Basic Social Organizations. Method: In materials and methods, the work corresponds to a field investigation; explanatory level. The information was obtained with a questionnaire and a Certificate of interviews using ordinal scales. The study population is represented by the Basic Social Organizations (230) and by the authorities of the Tacna Region (05). Result: The most important results are: Social Policy to Combat Poverty in the Tacna Region is poor, characterized by its welfarism and paternalism. Conclusion: it has been found that its productive capacity and entrepreneurship is minim